Diabetes and chronic kidney disease: a rare cause for a very common association - Fonseca, José Agapito; Jorge, Sofia; Gameiro, Joana; Lopes, José António; Guerra, José Oliveira (Journal of Clinical Nephrology, 2019)
The authors present the case of a 45-year-old female patient with diabetes and chronic kidney disease (CKD). She had unsatisfactory glycemic control, and showed some intellectual limitations. Her urine exam was unremarkable, and her renal ultrasound revealed single right kidney with aspects suggesting ureteropelvic junction syndrome. Her mother had also suffered from diabetes and CKD G5D presenting in the sixth to seventh decade. An hereditary cause for CKD was considered, which led the authors to investigate an autosomal dominant cause for CKD with a tubulointerstitial phenotype, taking into account the personal and family history for diabetes and also the renal imaging; a large deletion in the HNF-1β gene was identified through Multiplex Ligand Probe Assay (MLPA) analysis, explaining the phenotype. Genetic causes of CKD should be considered in the presence of positive family history for CKD, and the coexistence of diabetes with bland urine sediment should raise the possibility of a syndromic cause of the phenotype, namely involving HNF-1β gene mutations or deletions.